769 Indentifying deficiencies in stability, dynamic handling and rollover crashworthiness of quad bikes. (1st September 2016) - Grzebieta, Raphael; Rechnitzer, George; Simmons, Keith; Hicks, David; Sherry, Drew; Nevo, Ross Dal; McIntosh, Andrew
Abstract : Background: Currently, in Australia there are around 270, 000 quad bikes (ATVs) and Side by Side Vehicles (SSVs) in use, an estimated 80, 000 Quad bikes and SSVs in New Zealand, and an estimated 10 million Quad bikes and SSVs in the USA. Analysis of Australian Coronial data from 2001 to 2012 identified around 141 fatalities involving quad-bikes and SSVs. In comparison 2, 718 quad-bike fatalities occurred in the US in the years 2000 to 2010. Fatality data indicates that rollover, pinned entrapment and asphyxiation are the major casual factors in farm place deaths related to quad-bikes. As a result, the authors critically evaluated quad bike static stability, dynamic handling and rollover crashworthiness to identify engineering design deficiencies and possible countermeasures to reduce rollover injury risk. Methods: A major three year project comprised of over 1000 tests on a selection of 17 vehicles consisting of 8 quad bikes, 3 recreational quad bikes, 5 SSVs and a modified prototype quad bike. Testing was carried out at the NSW state government's Crashlab testing facility, consisting of ststic stability, dynamic handling and rollover crashworthiness tests. Results: Results from all the test program are presented, with links provided to the extensive project and Crashlab test reports. Conclusions: Deficiencies in the stability and handling of quad bikes which significantly increased the rollover risk with consequent increased risk of severe injury and death in the farming environment were identified and quantified. For the first time, the comparison of quad bikes with SSVs identified the superior static stability, dynamic handling, minimal disturbance of steering when traversing a bump, and rollover crashworthiness of SSVs. Quad bikes are not the best choice for workplace and farm vehicles but rather well designed SSVs, in general, are the more appropriate 'fit for purpose' vehicle choice.